Research on numerical simulation for partial discharge of epoxy interface excited by high‐frequency sinusoidal voltage. (14th October 2021) - Wang, Jian; Guo, Rui; Ping, An; Liu, Tao; Han, Shuai; Li, Qingmin
Abstract: High‐frequency sinusoidal voltage excitation is proposed as a feasible method to solve the difficulty of partial discharge detection at the epoxy interface. In order to study the development process of partial discharge under high‐frequency stress, a two‐dimensional plasma simulation model of partial discharge for a needle‐plate electrode structure is established by coupling particle transport equation, Poisson equation and plasma chemical reaction. The model adopts a reaction set to reduce the difficulty of modelling generation, transport and disappearance of charged particles. It realises dynamic simulation of the partial discharge at the epoxy interface. The spatial–temporal distribution characteristics of microscopic parameters such as electron density, electron temperature and surface charge are obtained. Based on this simulation model, the partial discharge characteristics of the epoxy interface at different frequencies are further studied in this work. The results show that with the increase of applied voltage frequency, the electron temperature shows an increasing trend, but its increasing rate gradually slows down; while surface charge accumulation decreases uniformly with the increase of applied voltage frequency. These two factors make the partial discharge severest under the frequency of 10 kHz. The results of the model are verified from two aspects of discharge form and discharge intensity by experimental means.